Bedri Noyan Dedebaba’s Doctoring - Altı, Aziz (Journal of Alevism-Bektashism Studies, 2023)
Bedri Noyan who was born in Serez, which is today a city in Greece in 1912, completed his primary and secondary education in various parts of Anatolia. He started his higher education at Istanbul University Faculty of Medicine in 1931. Noyan, who managed to establish good dialogues with his professors and friends during his student years at the Faculty of Medicine, also had an active student life by participating in social activities. He completed his education at Istanbul University Faculty of Medicine and graduated from there in 1937. Noyan, who started his medical career in 1937, went to the military in the same year to fulfill his national duty. After completing his military service, he worked as an assistant at the Hygiene Institute of Istanbul University Faculty of Medicine for a while. Later Noyan did his specialization in the ear, nose, and throat clinic at Ankara Numune Hospital. Afterwards, he worked as a specialist in Diyarbakır and Gaziantep hospitals. Noyan, who also served as the president of Diyarbakır Community Center for a while during his time in Diyarbakır, carried out studies on public health while in this position. In 1946, he successfully passed the exam at Istanbul University Faculty of Medicine and received the title of associate professor in the field of ear, nose and throat. He worked as a faculty member at Istanbul University Faculty of Medicine from 1946 to 1951. Noyan who left his teaching position at the university in 1951, started working as a freelance doctor in Aydın. Noyan, who converted to Bektashism in 1958, was elected to the position of “Dedebaba” in 1960, after the positions of dervish, baba and halifebaba. Noyan served in the dedebaba position, known as the highest rank of the Babagân branch of Bektashism, for 37 years. Bedri Noyan Dedebaba actively practiced medicine until 1987. Noyan, who has a versatile personality, also reflected his feelings about medicine in the Sufi-themed lines he wrote. Noyan has made significant contributions to the medical literature with his studies. In this article, Bedri Noyan Dedebaba’s doctoring history has been tried to be discussed.
Keywords: Bedri Noyan; Bektashi; Dedebaba; Doctor; Babagân